Die Bibel im Religionsunterricht ins Gespräch bringen - Dihle, Ariane (Forum Exegese und Hochschuldidaktik: Verstehen von Anfang an, 2022)
This article formulates challenges for university didactics on the basis of the situation in schools. It asks, which exegetical, hermeneutical and theological questions a teacher must have answered in order to be able to use the Bible in the classroom and how the study of Protestant theology can adequately prepare teachers for the challenges of teaching. Six different examples from school practice are used to explain what demands the subject of religious education places on teachers and what problem areas exist. Finally, the tension between academic studies and studies that are designed with practice in mind is addressed.